Advanced Microsoft Excel 2019 - Ashby, Deborah ([Packt Publishing], 2019)
"Get beyond the basics and supercharge your current skill level in Excel. With this 9-hour, expert-led video training course, you'll gain an in-depth understanding of more advanced Excel features that delve into high-level consolidation, analysis and reporting of financial information. Upon completion of this course, you'll be able to create charts that have an impact from databases that communicate data and financial records efficiently and effectively. You will be able to report data in various formats including: tables, graphs and PivotTables. Once completed you'll have advanced understanding of Excel that will positively impact your professional capability."--Resource description page